Exploring the Antimicrobial Activity of Quince Seeds Extracted by Two Different Methods - Eman Tareq Mohammed (University of Mosul, 2023)
Background: The rise of resistance to numerous effective antimicrobic drugs and the necessity to investigate alternative agents to address this emerge are conspicuously underscored. Aim: The aim is to evaluate the TPC (total phenolic contents), TFC (total flavonoidal contents), and the antimicrobial activity of two quince seeds extracts and their combination with commercial antimicrobial drugs. Methods: In this work two ethanolic extracts (Qu-1 and Qu-2) were prepared from quince seeds using two methods, microwave (M.wv) and sequential microwave-sonication assisted extraction (MSAE). The quantification of total phenolic content TFC and total flavonoid content TFC in these extracts were conducted using Folin-Ciocalteu and AlCl3 method respectively. The extracts, along with its combination with conventional antibiotics were tested for antimicrobial activity against a variety of aerobic and anaerobic bacteria using ciprofloxacin and metronidazole as references, respectively. The extracts were also tested against fungi (C. albicans and A. niger) using the standard, nystatin. Results: TPC and TFC for Qu-1 were 2.2578±1.82 μg GAE/g crude solid, 1.4901±1.76 μg RU/g crude solid respectively, while these values for Qu-2 were 1.0341±2.05 μg GAE/g and 0.7342±1.53 μg RU/g. Both extracts showed antimicrobial effectiveness against all examined pathogens with Qu-1 showing superior effectiveness. So, there is a positive association between TPC, TFC and antimicrobial activity. The combination of Qu-1 can enhances both the antifungal and anti-aerobic effects of NYS and CIP by reducing MFC and MBC and their corresponding potency factor. On the contrary, the Qu-2-antibiotic combination does not show any modification. Both extracts have microbicidal activity based on MBC/MIC ratio which is lower than 4. Conclusion: Quince seed extracts, especially Qu-1, show promise in fighting microbial infections. They could be used alone or in combination with antibiotics. Further research and development may lead to the development of new antimicrobials to address the growing issue of resistance.